Intervention Strategy for Ecosystem-Based Tourism Sustainability in Coastal Areas and Gili Matra Small Islands: Strategi Intervensi Untuk Keberlanjutan Wisata Pesisir Dan Pulau-Pulau Kecil Gili Matra Berbasis Ekosistem - Wibisana, Sri Yanti (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2021)
The development of coastal ecosystem-based tourism in Gili Matra has been very massive and tends to exceed capacity. For this reason, it is necessary to review the existing ecosystem status in mapping out appropriate intervention strategies in tourist areas. The research during 2021 at 13 locations in Gili Matra aims to look at the pattern and status of the ecosystem for the preparation of tourism development intervention strategies. Data analysis includes descriptive and cluster analysis of the pattern of ecosystem structure, habitat, and resources. The results showed that 30.7% of hard coral cover was still in good condition, and 69.23% was in poor condition. The coral health index level is also with the same percentage value as coral cover. Meanwhile, fish species richness that exceeds 5 species reaches 61.53% and less than 5 species by 38.46%. The general conclusion is that coral reefs are under pressure, although fish biodiversity is still high. The intervention strategy is through efforts to increase coral coverage, and while fishing tourism activities must be managed properly, so as not to damage coral reefs and maintain the target fish population.